Predictive Models of Compressive Strength Concrete Produced from Recycled Concrete Aggregate - Ngekpe, B. E.; Burabari, J.; Ukpaka, C. (International Journal For Research In Mechanical & Civil Engineering, 2018)
The investigation in this research is targeted at evaluating the most favourable proportion inclusion of RA as a partial replacement for NA to produce a grade-30 concrete using different water cement ratio of 0.40, 0.45 and 0.50. Experimental results indicate that 15%RA replacement gave a targeted compressive strength using different water cement ratios of 0.40- 0.50. However, an acceptable compressive strength of 30Mpa and above was achieved for 30%RA replacement with w/c ratios of 0.4 and 0.45 after 28days curing. Mathematical tools known as least square model and the polynomial regression model were used to predict and monitor the compressive strength of concrete; whereas, developing models for different W/C ratio and %RCA for 7, 14 and 28days was considered useful in predicting and monitoring compressive strength of concrete as validation of developed models equation revealed range of coefficient of determination (R2) of 0.80-0.97 by approach of ANOVA.